Effectiveness evaluation of complex information security systems in telecommunication systems - Конахович, Г.Ф.; Луцький, М.Г. (Proceedings of National Aviation University (archive), 2010)
Grounded criterion for protection of TCS based on technical and economic characteristics and indicators of TCS, the systems of attacks on information resources and information security systems.